Peningkatan Literasi Perbankan Syariah Pada Masyarakat Desa Pasar Ketahun Kecamatan Ketahun Kabupaten Bengkulu Utara - Tirta Investama; Asnaini Asnaini; Aan Shar (Yayasan Darussalam Bengkulu, 2024)
Public literacy related to Islamic banking is still very low compared to conventional banks. The purpose of this study is to provide knowledge about Islamic banks, change the perception of the people of Pasar Ketahun Village who think that Islamic banks are the same as conventional banks and provide motivation to use Islamic banks in everyday life. Community service was carried out in Pasar Ketahun Village, Ketahun District, North Bengkulu Regency. In this community service activity, researchers used direct practical research methods, with survey, interview, and documentation methods. From the results of the research in the form of socialization to the people of Pasar Ketahun Village, it provided knowledge and increased understanding and insight into the community regarding Islamic banks and there was an interest in using Islamic banks in everyday life.